2016
DOI: 10.4103/0973-6247.187946
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mirasol pathogen reduction system by artificially contaminating platelet concentrates with Staphylococcus epidermidis: A pilot study from India

Abstract: Background and Objectives:This study was conducted to assess the efficacy of Mirasol pathogen reduction system for platelets aimed at preventing bacterial regrowth by spiking buffy coat pooled platelets (BCPP) with clinically relevant load of Staphylococous epidermidis.Materials and Methods:BCPP units were prepared using Teruflex BP-kit with Imugard III-S-PL (Terumo BCT, Tokyo, Japan). Two BCPP units were pooled, of which 40 ml of negative control (NC) was removed. The remaining volume of the platelet unit was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Pathogen-reduction technology offers an attractive method to reduce transfusion-related infection risks. Several studies have shown that this technology can reduce the risk of pathogen transmission due to contaminated blood transfusions [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen-reduction technology offers an attractive method to reduce transfusion-related infection risks. Several studies have shown that this technology can reduce the risk of pathogen transmission due to contaminated blood transfusions [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method is effective against pathogens such as bacteria, Plasmodium spp, Leishmania, Ebola virus (4.5 log reduction), MERS-CoV (around 3.5 log reduction) and Chikungunya virus (78,79,80,81,82) but treatment still does not eliminate the potential risk of some viruses which may remain viable (83). In Figure 3 the effectiveness on bacteria are shown.…”
Section: Mirasol Prt Systemmentioning
confidence: 99%
“…However, to obtain high rates of agent titer reduction could often be unnecessary and in some cases "log reduction" may not be a good parameter to estimate the blood safety (107). In fact, it is important to consider that bacterial concentration is not very high shortly after collection and production (generally < 100 CFU/product), so a high log reduction capacity is not necessary (108,79). Instead, possible toxins produced during proliferation or lysis of pathogens are not inactivated by any avaible technology.…”
Section: Efficacymentioning
confidence: 99%
“…Bacterial contamination in blood transfusion products remains a significant risk for patients facing transfusion, particularly with platelet (PLT) components that have been stored at room temperature 5 . To reduce the risk of transfusion‐transmitted septic reactions, photodynamic inactivation of bacteria with ultraviolet (UV) or visible light, with or without photosensitizers, has been developed and can be applied to some transfusion products including PLTs and plasma 6–11 . Photosensitizers are molecules that convert light energy into chemical energy and amplify the biologic effects of light 12 .…”
Section: Introductionmentioning
confidence: 99%